Dawn of a new era - Abd Razak, Dzulkifli (2007)
The world premiere of The New Dawn was held at an open air geodesic theatre last weekend at the wellknown Penang Hill. With the flickering lights of George Town, providing a backdrop, the event was a glittering performance of world standard, featuring the internationallyrenowned Ramli Ibrahim and the Sutra Dancers. Two Japanese master musicians were also in the programme. The event lived up to its designation of being the "new dawn", not only due to the superb dance and musical presentations but, quite uniquely, the panoramic theatrical styles that naturally blended with the cool night breeze.